Colonial Girlhood - Moruzi, Kristine; Smith, Michelle J. (Australasian Journal of Victorian Studies, 2013)
Settler colonies and colonies of occupation, such as Canada, Australia, New Zealand, India, Ireland, South Africa, and the Caribbean, held out the possibility for girls to experience freedom from, and the potential to reconfigure, British norms of femininity. This special issue of the Australasian Journal of Victorian Studies on colonial girlhood seeks to examine how colonial girlhood was constructed and redefined in colonial texts and cultures. It also explores the transnational influence of these ideologies of girlhood as they circulated throughout the British empire and elsewhere.